Empowering disabilities through public speaking: Building social independence with a co-creation approach - Ike Desi Florina; Sri Adi Nurhayati; Inas Sanny Muyassaroh; Sesya Dias Mumpuni (Universitas Muhammadiyah Magelang, 2024)
Tegal Regency continues to grapple with discrimination and stigma against people with disabilities, leading to insufficient social support, low self-confidence, and communication barriers. This limited communication hinders their social independence. This activity aimed to enhance self-confidence, public speaking skills, and social independence among members of Difabel Mandiri Slawi (DMS). The program comprised three stages: (1) An initial Focus Group Discussion (FGD) with DMS in July 2024 to assess needs; (2) Motivational seminars and public speaking workshops (incorporating theory and practice); and (3) Co-creation activities, including public speaking practice at Alun-Alun Slawi. The program successfully increased participants' self-confidence by 47% and their public speaking skills by 50%, positively impacting their social independence as evidenced by improved social relationships.